Performance at slaughter and beef quality characteristics of some Mediterranean beef breeds compared to Central and North European breeds (GemQual EU Project) - Gigli S.; Failla S.; Iacurto M.; Contò M.; Sañudo C.; Olleta J.L.; Albertí P.; Panea B.; Hocquette J.F.; Ertbjerg P.; Christensen M.; Nute G.R.; et al. (Mediterranean livestock production: uncertainties and opportunities, 2008)
This work is part of a European Project called GemQual (Genetics of Meat Quality), which aims to define genetic components of meat quality, taking into consideration measurements on different European breeds. In Europe, consumers show different preferences regarding beef quality characteristics in accordance with geographical areas. The study of these quality characteristics is therefore of importance. Young bulls were reared and slaughtered in 5 countries by the GemQual partners using standardized protocols. In this paper, only performance and quality meat data of beef cattle subdivided in two groups are presented. The first group corresponds to Mediterranean breeds (Med: Asturiana de los Valles, Charolais, Limousin, Marchigiana, Piemontese and Pirenaica) and the second group to North European breeds (NorthE: Aberdeen Angus, Simmental and South Devon). The fatness score was lower in the Med animals (2+ vs 3) particularly for the double muscle animals (1+). The less fatty animals showed on the contrary a higher meat percentage (+7.3%). Med group showed a good lightness (44.02 vs 40.25) and higher values of redness and yellowness of their meat (15.62 vs 12.22, 15.13 vs 12.71 respectively). Total pigments showed higher value for Med group (approximately +4%), particularly due to oxymyoglobin content significantly higher compared to NorthE group (+2.1%). In conclusion, quality meat appears different between groups, Mediterranean breeds being characterized by a lower fat percentage in the carcass and a light meat.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)